Innovation at the Firm Level across Countries with Different Economic and Technological Capacity - Andreas Reinstaller; Fabian Unterlass (Austrian Institute of Economic Research (WIFO), 2012)
This paper presents an analysis of innovation behaviour at the firm level across countries with different levels of technological capabilities and economic development. Using data from the Community Innovation Survey for 20 European countries the paper shows that the impact of total innovation expenditures - including next to R&D also outlays for technology transfer, the market introduction of innovations or new designs - increases monotonically across countries with their level of technological capabilities. R&D investments instead have a significant impact on the generation of innovations only for firms located in countries with higher levels of technological capabilities. Firm specific competencies to suggest or contribute to innovation projects have a more significant effect on the innovation output the higher the level of economic development of the countries in which firms are located. Finally, the paper presents also evidence that R&D does not generally increase the absorptive capabilities of firms.
Keywords: 330; Innovation decision; Catching up; Technological capabilities; R&D; Industrieforschung; Technischer Fortschritt; Technologiewahl; Wirtschaftliche Konvergenz; Europa